2012
DOI: 10.1080/1360144x.2011.616049
|View full text |Cite
|
Sign up to set email alerts
|

Developing new academic developers: doing before being?

Abstract: A small group of new academic developers reflected on their induction into the profession and wondered if things could have been done differently. The researchers decided to question the directors of three tertiary academic development units about how they recruited new developers, what skills and competences they looked for and how they inducted new appointees into the role. This article interrogates the interview data, employing Winter's 'dilemma analysis' to tease out the ambiguities, judgments and problems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…It is these ambiguities (Clegg, 2009;Kensington-Miller et al, 2012;Manathunga, 2006) that have led to finding new ways of working, in this case accessing Twitter as a conversational platform that enables professional local and global connections. We have found that the inbetween zone we inhabit as academic developers is enhanced and positively disrupted through our use of Twitter because old hierarchical ways of working are navigated more easily or even bypassed, thus allowing for unexpected opportunities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is these ambiguities (Clegg, 2009;Kensington-Miller et al, 2012;Manathunga, 2006) that have led to finding new ways of working, in this case accessing Twitter as a conversational platform that enables professional local and global connections. We have found that the inbetween zone we inhabit as academic developers is enhanced and positively disrupted through our use of Twitter because old hierarchical ways of working are navigated more easily or even bypassed, thus allowing for unexpected opportunities.…”
Section: Resultsmentioning
confidence: 99%
“…In academic development, one way of working involves a disposition of openness (Clegg, 2009;Kensington-Miller et al, 2012) and having an interest in learning from others through networking and sharing. In her reflection, Author C noticed that she has 'conversations and relationships with people' and that we have these 'online and through time'.…”
Section: Entanglement Reflection and Diffractionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are comparatively fewer contributions on how we develop the knowledge and skills for the practice we engage in. Some articles showcase individuals' paths into academic development work and identities (Fyffe, 2018;Jessop et al, 2018;Kensington-Miller et al, 2015), while Kensington-Miller et al (2012) explored whether 'there is a best way to develop the next generation of academic developers ' (p. 131) through interviews with directors of educational developmentand the simple answer was 'no'. But the need for professional development opportunities was strongly argued.…”
Section: Introductionmentioning
confidence: 99%
“…We initiated this course because we share a concern with many seasoned academic developers from around the world about the need to ensure that novices are inducted into the field in ways that are much more systematic than that has been the case up to now (see, for example, Kensington-Miller, Brailsford, &Gossman, 2012 andQuinn &Vorster, 2014). Academic development (AD) work is varied, specialised and complex.…”
Section: Introductionmentioning
confidence: 99%